Publisher Correction: Antibody and TLR7 agonist delay viral rebound in SHIV-infected monkeys. (6th December 2018) - Borducchi, Erica; Liu, Jinyan; Nkolola, Joseph; Cadena, Anthony; Yu, Wen-Han; Fischinger, Stephanie; Broge, Thomas; Abbink, Peter; Mercado, Noe; Chandrashekar, Abishek; Jetton, David; Peter, Lauren; et al.
In Fig. 4b of this Article, the x-axis labels 'PGT121' and 'GS-9620' were inadvertently swapped in both graphs. In Fig. 5a, b, 'TLR7' should have been 'GS-9620'. These figures have been corrected online.